Analysis Location, Word Of Mouth and Security Against the Decision to Purchase Permata Buana Kembangan Housing in West Jakarta - Amzad Samudro; Hamdan Hamdan; Abdul Rahmat (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This research is about the decision to buy housing at Permata Buana Kembangan, West Jakarta and this study aims to determine the effect of location, word of mouth, and security on purchasing decisions for Permata Buana housing and respondents who will buy Permata Buana housing. This research is descriptive and quantitative. Primary data and secondary data were obtained. Secondary data was obtained from various sources such as journalists, books, and primary data for other related publications obtained by distributing questionnaires to target respondents. Determination of the number of samples using the purposive sampling technique will be distributed via google form to 83 respondents obtained. The results showed that Location had a significant relationship with purchasing decisions, Word of Mouth was not significant for purchasing decisions, and Security was not significant for purchasing decisions.